The right ventricle under pressure: Anatomy and imaging in sickness and health. Issue 1 (13th March 2022) - Stubbs, Harrison; MacLellan, Alexander; Lua, Stephanie; Dormand, Helen; Church, Colin
Abstract: The right ventricle (RV) is an important structure which serves a multitude of vital physiological functions in health. For many years, the left ventricle has dominated the focus of understanding in both biology and pathophysiology and the RV was felt to be more of a passive structure which rarely had an effect on disease states. However, it is increasingly recognised that the RV is essential to the homoeostasis of normal physiology and disturbances in RV structure and function have a substantial effect on patient outcomes. Indeed, the prognosis of diseases of lung diseases affecting the pulmonary vasculature and left heart disease is intimately linked to the function of the right ventricle. This review sets out to describe the developmental and anatomical complexities of the right ventricle while exploring the modern techniques employed to image and understand its function from a clinical perspective. Abstract : The RV is essential to the homeostasis of normal physiology and disturbances in RV structure and function has a substantial effect on patient outcomes. This review sets out to describe the developmental and anatomical complexities of the right ventricle while exploring the modern techniques employed to image and understand its function from a clinical perspective.